Fatal toxoplasmosis in Little Penguins (Eudyptula minor) from Penguin Island, Western Australia. (April 2022) - Campbell, Kym; Paparini, Andrea; Gomez, Adriana Botero; Cannell, Belinda; Stephens, Nahiid
Abstract: Routine post mortems of deceased penguins from Penguin Island, Western Australia, found that a temporal cluster of cases presented with characteristic gross and microscopic changes, namely birds in good body condition with hepatomegaly and splenomegaly, multifocal hepatic and splenic necrosis and numerous, 1–2 μm diameter protozoan parasites within the necrotic foci. Electron microscopy identified the protozoa as belonging to the phylum Apicomplexa. Molecular investigations by PCR gave inconsistent results. PCR performed by an external laboratory identified a novel Haemoproteus spp. organism in samples from 4 of 10 cases from this group, while PCR at Murdoch University identified Toxoplasma gondii in 12 of 13 cases (including 9 of the 10 assayed at the external laboratory). Immunohistochemistry of formalin fixed tissues also identified Toxoplasma in the hepatic and splenic lesions. The distinctive mortalities which were observed in this group of penguins are attributed to a fulminant toxoplasmosis, with a concurrent Haemoproteus infection in some cases. Though the clinical signs of infection are unknown, the gross and microscopic appearance at post mortem is sufficiently characteristic to allow a diagnosis to be made on these features. Definitive confirmation of Toxoplasma infection can be made by immunohistochemistry or PCR. Graphical abstract: Image 1 Highlights: Deaths in Little Penguins were associated with necrosis in the liver and spleen. The necrotic lesions contained protozoa, free and in cysts. The protozoa were identified as Toxoplasma by PCR and immunohistochemistry.